Meaning Construction of Public Relations Managers in Higher Education Institutions - Winda Eka Putri; Hanny Hafiar; Feliza Zubair (Jurnal Komunikasi, 2025)
The increasingly competitive dynamics of higher education have led to an increase in the strategic role of public relations managers in managing institutional reputation. In this context, this study aims to understand how university public relations managers construct the meaning of their profession through life experiences, social relations, and institutional pressures and expectations in the work environment. A qualitative method with Alfred Schutz's phenomenological approach was used to explore the subjective meanings formed from the daily experiences of the informants. Meanwhile, Berger and Luckmann's social construction theory served as a conceptual framework to explain how professional meaning is formulated through the processes of externalisation, objectification, and internalisation within the organisational structure of higher education institutions.This study involved in-depth interviews with five university public relations managers in Indonesia. The results show that professional meaning is formed through a dialectic between past experiences (because motives), future goals (in-order-to motives), and social dynamics within the organisation that shape their views on the role of public relations. This process encourages a shift in professional identity from merely technical communication implementers to strategic actors who play a role as reputation navigators at the national and global levels.These findings make an important contribution to the development of competencies and the design of public relations organisational structures in higher education institutions. In addition, this research emphasises the need to strengthen the strategic capacity and communicative sensitivity of public relations managers so that they are able to respond to the complexity of the higher education ecosystem in Indonesia and strengthen the reputation of institutions in a sustainable manner.